Farnesol Ameliorates Demyelinating Phenotype in a Cellular and Animal Model of Charcot-Marie-Tooth Disease Type 1A - Na-Young Park; Geon Kwak; Hyun-Myung Doo; Hye-Jin Kim; So-Young Jang; Yun-Il Lee; Byung-Ok Choi; Young-Bin Hong (Current Issues in Molecular Biology, 2021)
Charcot-Marie-Tooth disease (CMT) is a genetically heterogeneous disease affecting the peripheral nervous system that is caused by either the demyelination of Schwann cells or degeneration of the peripheral axon. Currently, there are no treatment options to improve the degeneration of peripheral nerves in CMT patients. In this research, we assessed the potency of farnesol for improving the demyelinating phenotype using an animal model of CMT type 1A. In vitro treatment with farnesol facilitated myelin gene expression and ameliorated the myelination defect caused by PMP22 overexpression, the major causative gene in CMT. In vivo administration of farnesol enhanced the peripheral neuropathic phenotype, as shown by rotarod performance in a mouse model of CMT1A. Electrophysiologically, farnesol-administered CMT1A mice exhibited increased motor nerve conduction velocity and compound muscle action potential compared with control mice. The number and diameter of myelinated axons were also increased by farnesol treatment. The expression level of myelin protein zero (MPZ) was increased, while that of the demyelination marker, neural cell adhesion molecule (NCAM), was reduced by farnesol administration. These data imply that farnesol is efficacious in ameliorating the demyelinating phenotype of CMT, and further elucidation of the underlying mechanisms of farnesol’s effect on myelination might provide a potent therapeutic strategy for the demyelinating type of CMT.